Pandemic-Intensified Motherhood: Making Sense of Increased Mothering Pressures during COVID-19 - Limonic, Laura (Journal of the Motherhood Initiative for Research and Community Involvement, 2023)
The COVID-19 pandemic and resultant stay-at-home orders and school shutdowns initiated a period of unprecedented household labour and childrearing for families across the world. Through in-depth qualitative interviews with seventy-six mothers from across the United States, I examine the increased demands placed on mothers as a result of the stay-at-home orders and the role of existing social and structural factors in fostering and maintaining these demands. I utilize the lens of intensive mothering to understand how mothers made sense of the augmented workload during the pandemic as well as the ways intensive mothering influences how mothers adapt to and meet these increased demands.